2020
DOI: 10.3390/pr8030294
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Suppression Effects of Inert Powders on the Minimum Ignition Temperature and the Minimum Ignition Energy of Polyethylene Dust

Abstract: The risks associated with dust explosions still exist in industries that either process or handle combustible dust. This explosion risk could be prevented or mitigated by applying the principle of inherent safety. One effective principle is to add an inert material to a highly combustible material in order to decrease its ignition sensitivity. This paper deals with an experimental investigation of the influence of inert dust on the minimum ignition temperature and the minimum explosion energy of combustible du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…KHCO 3 has often been used to inhibit nano PMMA dust, aluminum powder, and industrial dust explosions. Studies have shown that the smaller the particle size of KHCO 3 powder, and the higher the powder concentration, the stronger the explosion inhibition effect. Meanwhile, numerous scholars have found that powder inhibitor KHCO 3 can significantly inhibit methane/air explosions. For example, Babushok et al studied the combustion rate and temperature suppression effect of premixed CH 4 /air flame with the addition of KHCO 3 , and the reduction in the combustion rate was attributed to the thermal effect of the added additives, reducing the concentration of free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…KHCO 3 has often been used to inhibit nano PMMA dust, aluminum powder, and industrial dust explosions. Studies have shown that the smaller the particle size of KHCO 3 powder, and the higher the powder concentration, the stronger the explosion inhibition effect. Meanwhile, numerous scholars have found that powder inhibitor KHCO 3 can significantly inhibit methane/air explosions. For example, Babushok et al studied the combustion rate and temperature suppression effect of premixed CH 4 /air flame with the addition of KHCO 3 , and the reduction in the combustion rate was attributed to the thermal effect of the added additives, reducing the concentration of free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [11] added NaHCO 3 to aluminum powder and found that it could reduce the thickness of the flame reaction zone and weaken the flame propagation rate. Lin et al [12] studied the effect of four inert powders (NaHCO 3 , NaC 2 O 4 , KHCO 3 and K 2 C 2 O 4 ) on the minimum ignition energy (MIE) and minimum ignition temperature of polyethylene dust, and found that the suppression effect of bicarbonate dust was better than that of oxalate dust. Jiang et al [13] studied the inhibition effect of NaHCO 3 with different particle sizes on the explosion of aluminum powder and concluded that NaHCO 3 hinders the explosion of aluminum powder by both physical inhibition and chemical inhibition; however, they compared the inhibition of combustion of aluminum powder by NH 4 H 2 PO 4 and NaHCO 3 and pointed out that NH 4 H 2 PO 4 has a better inhibition effect [14].…”
Section: Introductionmentioning
confidence: 99%
“…In this Special Issue, "Thermal Safety of Chemical Processes", we aim to present the relevance and diversity of this research area. In particular, the issue proposes some research in the field of thermal parameters measurement [5], in the prediction of lithium-ion battery thermal runaway [6], and in thermal analysis of vacuum resistance furnace [7] or dust explosion [8].…”
mentioning
confidence: 99%
“…In [8], the authors developed an inherent safety-based approach to mitigate risks associated with dust explosions in industries that either process or handle combustible dust. Such an approach consists in adding an inert material to a highly combustible material in order to decrease its ignition sensitivity.…”
mentioning
confidence: 99%